Second language and heritage learners in mixed classrooms - Bayona, Patricia 1970-; García-Martín, Elena (New perspectives on language and education, 2022)
This book addresses the complexity of mixed language classroom learning environments in which heritage learners and second language learners are concurrently exposed to language learning in the same physical space. It offers best practices and reproducible pedagogical initiatives and methodologies for different levels of instruction